Polymorphism in Cytochrome P450 3A4 Is Ethnicity Related - Guttman, Yelena; Nudel, Adi; Kerem, Zohar (Frontiers in Genetics, 2019)
Can mutations in cytochrome P450 3A4 (CYP3A4), the major food- and drug-metabolizing enzyme, serve as biomarkers for personalized precise medicine? Classical genetic studies provide only limited data regarding the frequencies of CYP3A4 mutations and their role in food-drug interactions. Here, in an analysis of one large database of 141,456 individuals, we found 856 SNPs (single nucleotide polymorphism), of which 312 are missense mutations, far more than the previously reported dozens. Analyzing the data further, it is demonstrated that the frequency of mutations differs among ethnic groups. Hierarchical clustering divided the mutations into seven groups, each corresponding to a specific ethnicity. To the best of our knowledge, this is the first comprehensive analysis of CYP3A4 allele frequencies in distinct ethnic groups. We suggest ethnicity based classification of CYP3A4 SNPs as the first step towards precise diet and medicine. Understanding which and when polymorphism might have clinical significance is a tremendously complex task. Using a modeling approach, we could predict changes in the binding poses of ligands in the active site of single variants. These changes might imply clinical effects of the overlooked protein-altering CYP3A4 mutations, by modifying drug metabolism and FDI. It may be concluded that dietary habits, and hence FDI, are matters of ethnicity. Consequently, ethnic-related polymorphism in CYP3A4 and diet may be one underlying mechanism of response to medical regimes. The approaches presented here have the power to highlight mutations of clinical relevance in any gene of interest, thus to complement the arsenal of classic genetic screening tools.